S poznavanjem prehranskih vrednosti živil do uravnoteženega prehranjevanja - Dolinar, Jelka (Farmacevtski vestnik, 2022)
The selection and preparation of food is a daily task for every household. Pharmacists, interdisciplinary trained health professionals, can, based on food composition values, individual eating habits, health status, and lifestyle, assess whether an individual's diet is balanced or whether an additional food supplement intake is required. We present some of the main causes of potential nutrient losses in food during the preparation of food for its own use and the impact on the bioavailability of nutrients from food. We compiled a menu with an energy value of about 2000 kcal (i.e. 8368 kJ) and compared food composition values in five different national food databases. We determined the energy value of food, the total content of macronutrients, and some micronutrients, according to the recommended daily intake, from which we selected six minerals and ten vitamins. The results differ between databases, but all five databases allow quite an usefull assessment of food nutrition values, which is the basis for dietary recommendations.
Keywords: food; food databases; Hrana; macronutrients; makrohranila; micronutrients; mikrohranila; nutrition values; podatkovne zbirke; prehranska vrednost